PURIFYING TURBID WATER BY MORINGA SEEDS AND SAND FILTER METHODE AT NORTH HUIDU VILLAGE, GORONTALO DISTRICT, INDONESIA - Zulfiayu Sapiun (International Interdisciplinary Conference on Sustainable Development Goals, 2019)
Water is a essensial for live. Water for consumption purpose needs to be treated to meet the quality guidelines of 5 Nephelometric Turbidity Unit (NTU) according to World Health Organization. There was some treatment like the use of chemical water treatment agents, which are mostly imported and are usually very expensive, and toxic. The community of North Huidu have a serious problem with turbid water. The community service team of Health Polytechnic of Gorontalo want to solve this problem. Team introduce moringa seed and sand filter as purifier water. As an underutilized tree in Gorontalo Province, Moringa oleifera (drumsticks) seeds can be used as a coagulant agent that can purify turbid water. The community service was held at 21 November 2018 at Village Office of North Huidu and attended by 50 people. After the average of pretest was 73 and the average of post test was 82. It means there was a significant enhancement of knowledge about purifying water. Moringa seeds and sand filter can be used as effective purifier at North Huidu Village.